Proměny současných odborných komunikátů - Čechová, Marie (Stylistyka, 2023)
The paper reviews chan ges in the extent and con tent of the notion of specialist style. It draws inspiration from B. Havranek ( 1 932), continues a long its elaboration in the 50th (Fr. Travnicek, Fr. Dan es), at the tum of 60 and 70th (A. Jedlicka) and in the 90th (J .V. Becka, M. Jelinek, M. Ćechova). The attention is paid to defining of the borders between specialist and administrative styles, to relations between learning style with scientific and administrative ones, to position of aesthetic style and to changes within the scientific style.